2018
DOI: 10.1111/dth.12698
|View full text |Cite
|
Sign up to set email alerts
|

Anterior, frontal congenital triangular alopecia, redundancy in therapy without improvement

Abstract: Congenital triangular alopecia (CTA) is a benign noncicatricial localized pattern of hair loss with unknown etiology. Although referred to as “congenital,” CTA may develop in adulthood. It is believed that many cases of CTA are never diagnosed or are misdiagnosed; causing the incidence to be underestimated. The present study evaluates a case of 20‐year‐old woman presenting with a single circular to oval area of hair‐loss in the mid‐frontal region of her scalp. To date, about 170 cases of CTA have been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Histopathological reports in atypical CTA are very limited. While no previous anatomopathological de-Skin Appendage Disord 2021;7:387-392 DOI: 10.1159/000514698 scriptions exist in occipital Brauer nevus, the microscopical findings among specimen biopsies we performed seem to be the same as those found in the cases of frontotemporal impairment, as well as in the mid-frontal samples [1,12,13]: absence of mature hairs and the pres-ence of vellus hairs in the upper dermis. The total number of follicles present is normal, although follicular size is small for the scalp.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Histopathological reports in atypical CTA are very limited. While no previous anatomopathological de-Skin Appendage Disord 2021;7:387-392 DOI: 10.1159/000514698 scriptions exist in occipital Brauer nevus, the microscopical findings among specimen biopsies we performed seem to be the same as those found in the cases of frontotemporal impairment, as well as in the mid-frontal samples [1,12,13]: absence of mature hairs and the pres-ence of vellus hairs in the upper dermis. The total number of follicles present is normal, although follicular size is small for the scalp.…”
Section: Discussionmentioning
confidence: 57%
“…In the same way, affection of the mid-frontal scalp is even more outstanding, with only 2 cases reported in the literature so far [12,13]. Three out of 4 patients were males, all of them with a perinatal onset and an average age of dermatologist assessment of 16.7 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although two cases with congenital hair loss with vellus hair at the front area have been reported, 2,3 nevus sebaceus is included in the differential diagnosis of TTA and is sometimes hard to exclude. 2 The expression levels of AR in eccrine glands are higher in nevus sebaceus than those in healthy scalp. 4,5 AR expression levels in our case were within normal range.…”
Section: Temporal Triangular Alopecia Confined To the Frontal Scalpmentioning
confidence: 99%
“…Despite the typical presentation of CTA as a triangular or oval patch of circumscribed alopecia localized in the frontotemporal area, some authors reported atypical locations of CTA in the mid-frontal region of the scalp [10], the occipital area [11], the left temporo-parietal-vertex region of the scalp [12], and the eyebrows [13]. The diagnosis of CTA is mainly based on its clinical appearance and location.…”
mentioning
confidence: 99%